COMPARISON OF LEARNING STYLES AMONG POST GRADUATE RESIDENTS AND FULL TIME SPECIALTY CLINICIANS PURSUING HIGHER EDUCATIONAL DEGREE - Sahibzada Nasir Mansoor (Army Medical College Rawalpindi, 2019)
Objective: To compare the different learning style preferences among full time specialty clinicians and post graduate residents.